Optimalisasi Partisipasi Aktif Mahasiswa Melalui Experiental Learning Pada Program Merdeka Belajar Kampus Merdeka - Sismeri Dona; Dede Mahdiyah; Dwi Rahmawati; Fauji Nurdin (Indonesian Journal Publisher, 2024)
21st century learning can develop students' skills needed to live and work in a dynamic global era. The 21st century learning design can be carried out using research methodology based on experiential learning & collaborative practice. Strengthening 21st century skills can also be done using an experiential learning approach that is integrated with the Independent Campus Learning Program launched by the government. The method used in this service is the experiential learning method with stages, namely: preparation stage, observation stage, planning stage, activity implementation stage and evaluation stage of the process that has been undertaken and reflection stage. The target of this service is junior high school students in the Banjarmasin area. The final result of this activity is instilling student empathy towards the problems of community life, being able to work together across fields of science, and increasing the real role and contribution of universities and students in national development.